Genomic evolution of SARS-CoV-2 in Morocco: Insights from whole genome sequences collected from 2020 to 2024 - Hamza GHAMMAZ; Marouane MELLOUL; Ahlam MBARKI; Mouhssine HEMLALI; Taha CHOUATI; Hicham EL ANNAZ; Nadia TOUIL; Mostafa ELOUENNASS; Khalid ENNIBI; Elmostafa EL FAHIME (Virus Research)
This study investigates the evolution and genetic diversity of SARS-CoV-2 strains circulating in Morocco to track the spread, clade distributions and mutations of the virus across various regions from February 2020 to June 2024. The genome sequences were retrieved from the GISAID database. A total of 2630 SARS-CoV-2 genome sequences were analyzed using bioinformatic tools such as Nextclade, followed by phylogenetic and statistical analyses. The study highlights the predominance of the GRA clade (Omicron variant) since November 2021, while clades such as G, GH, GR, and GRY were identified earlier. The GRA clade exhibited the highest number of non-synonymous mutations, particularly in the Spike (S) gene, suggesting strong evolutionary pressure. The correlation analysis between structural and non-structural proteins revealed key interactions between S and NSP5, providing insights into the viral replication and assembly processes. This work gives new insights to the dynamics of SARS-CoV-2 in Morocco and underscores the importance of ongoing genomic surveillance to respond to emerging variants and potential future outbreaks.